2007
DOI: 10.1103/physrevc.76.028501
|View full text |Cite
|
Sign up to set email alerts
|

Schiff screening of relativistic nucleon electric-dipole moments by electrons

Abstract: We show, at leading-order in the multipole expansion of the electron-nucleus interaction, that nucleon electric-dipole moments are completely shielded by electrons so that they contribute nothing to atomic electric-dipole moments, even when relativity in the nucleus is taken into account. It is well known that relativistic electron motion, by contrast, leads to dipole moments that are not screened; we discuss the reasons for the difference. * Electronic address: cpliu@lanl.gov † Electronic address: engelj@phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Numerical evaluations of the Schiff moment [17] and their relation to the atomic EDM magnitude (for a few heavy atoms) are also known [18]. Further developments include, for example, a more general form of the Schiff moment obtained via calculations at the operator level [19], the evaluation of internal nucleon contribution to the Schiff moment [20], the enhancement of Schiff and octupole moments (by more than 2 orders of magnitude) in atoms with asymmetrically deformed nuclei with collective P and T-odd electromagnetic interactions [21], analysis of the Schiff theorem in ions and molecules [22], and other important results [23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical evaluations of the Schiff moment [17] and their relation to the atomic EDM magnitude (for a few heavy atoms) are also known [18]. Further developments include, for example, a more general form of the Schiff moment obtained via calculations at the operator level [19], the evaluation of internal nucleon contribution to the Schiff moment [20], the enhancement of Schiff and octupole moments (by more than 2 orders of magnitude) in atoms with asymmetrically deformed nuclei with collective P and T-odd electromagnetic interactions [21], analysis of the Schiff theorem in ions and molecules [22], and other important results [23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in each case a more careful analysis of this issue is required. In an atom, to first order the nucleon EDMs can be completely shielded by the electrons . However, in general the rather significant enhancement of the electron EDM due to relativistic electron motion has been found to survive.…”
Section: Systems To Search For Edmsmentioning
confidence: 99%
“…The P , T -odd N N interactions induce nuclear EDMs, but those are completely screened in neutral atoms due to the interactions with surrounding electrons. One of the leading contributions to the EDM of a diamagnetic atom arises from the nuclear Schiff moment (NSM) induced by the P , T -odd N N interactions [17][18][19]. The experimental precision has been improved for a long time in 199 Hg [20][21][22][23][24][25][26] and 129 Xe [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%